PENGARUH BUDAYA ORGANISASI, KOMPETENSI KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PROVINSI RIAU - Muslim, Dina Yonita; Setianingsih, Rahayu; Kusumah, Alum (Komunitas Manajemen Kompetitif, 2024)
ABSTRACT THE EFFECT OF ORGANIZATIONAL CULTURE, JOB COMPETENCE AND WORKLOAD ON THE PERFORMANCE OF EMPLOYEES OF DEPARTMENT EDUCATION PROVINCIAL RIAU This study aims to determine and analyze the effect of organizational culture, job competence and workload on the performance of employees of Departmen Education Provincial Riau. This research is a quantitative study with a research sampling method, namely the saturated sample Dispropotionate Stratified Random Sampling, which is a sampling technique when all members of the population are used as samples with a sample of 126 respondents. The data analysis method used in this research is multiple linear regression analysis using SPSS v. 24. The results of this study are organizational culture variables have a positive and significant effect on the performance of employees of Departmen Education Provincial Riau, job competence variables have a positive and significant effect on the performance of employees of Departmen Education Provincial Riau, and workload variables have a positive and insignificant effect on the performance of employees of Departmen Education Provincial Riau Keywords: Organizational culture, job competence, workload on the performance of employees.